CARICOM Perspective: A century of achievement (Georgetown, Guyana: The CARICOM Secretariat Communication Unit, 1999)
This edition highlight some of the issues facing the Caribbean at the end of the 20th Century.
CARICOM PERSPECTIVE is published once a year and reports on the work, achievements and problems of the Caribbean Community and is is issued free of charge to readers in the Community.
Keywords: Periodicals; Caribbean area; CARICOM; Caribbean Community